RELATIONSHIP BETWEEN P53 EXPRESSION AND PROBABILITY OF ORGAN CONFINEMENT IN PATIENTS WITH PROSTATE CANCER IN SARDJITO HOSPITAL - Soeroharjo, Indrawarman; Danarto, H R (Indonesian Journal of Urology, 2011)
Objective: To determine the association between p53 expression and the probability of organ confinement in patients with prostate cancer in Sardjito Hospital, Yogyakarta. Material & method: Prostate specimens were obtained from patients with clinical  stage  T1-T2 prostatic  adenocarcinoma  in Sardjito  Hospital between January  2007 and December 2008. Samples were processed and immunohistochemically stained in the Department of Anatomical Pathology Gadjah Mada University. Probability of organ confinement was determined by updated Partin table 2007 from preoperative serum PSA level, Gleason Score, and clinical stage. Correlation  between p53 expression and probability of organ confinement were statistically analyzed by Spearman correlation test. Results: There were 28 prostate cancer patients eligible for this study. Mean age was 65,19 ± 10,9 (28 - 81) years old. Mean preoperative PSA level were 107,13 ± 165,82 (0,20  734,20) ng/ml. Mean number of p53 expression was 97,47 ± 97,27 (5 - 396)/HPF. Significant correlation was found between p53 expression and probability of organ confinement (Spearman r = -0,441; p = 0,019). Conclusion:  p53 expression was negatively correlated with the level of organ confinement in patients with prostate cancer